Ultra‐High Pyridinic N‐Doped Porous Carbon Monolith Enabling High‐Capacity K‐Ion Battery Anodes for Both Half‐Cell and Full‐Cell Applications. Issue 35 (17th July 2017) - Xie, Yihao; Chen, Yu; Liu, Lei; Tao, Peng; Fan, Mouping; Xu, Na; Shen, Xiaowei; Yan, Chenglin
Abstract : An ultrahigh pyridinic N‐content‐doped porous carbon monolith is reported, and the content of pyridinic N reaches up to 10.1% in overall material (53.4 ± 0.9% out of 18.9 ± 0.4% N content), being higher than most of previously reported N‐doping carbonaceous materials, which exhibit greatly improved electrochemical performance for potassium storage, especially in term of the high reversible capacity. Remarkably, the pyridinic N‐doped porous carbon monolith (PNCM) electrode exhibits high initial charge capacity of 487 mAh g −1 at a current density of 20 mA g −1, which is one of the highest reversible capacities among all carbonaceous anodes for K‐ion batteries. Moreover, the K‐ion full cell is successfully assembled, demonstrating a high practical energy density of 153.5 Wh kg −1 . These results make PNCM promising for practical application in energy storage devices and encourage more investigations on a similar potassium storage system. Abstract : An ultrahigh pyridinic N‐doped porous carbon monolith (PNCM) with a 3D interconnected structure is fabricated by using melamine–formaldehyde resin as a hard template and a nitrogen source. The electrode delivers an extremely high reversible capacity of 487 mA h g −1 at 20 mA g −1 . A K‐ion full cell assembled with PNCM/3, 4, 9, 10‐perylene tetracarboxylic acid dianhydride demonstrates promising potential for practical applications.